Role of the Mitochondrial Pyruvate Carrier in the Occurrence of Metabolic Inflexibility in Drosophila melanogaster Exposed to Dietary Sucrose - Chloé J. Simard; Mohamed Touaibia; Eric Pierre Allain; Etienne Hebert-Chatelain; Nicolas Pichaud (Metabolites, 2020)
Excess dietary carbohydrates are linked to dysregulation of metabolic pathways converging to mitochondria and metabolic inflexibility. Here, we determined the role of the mitochondrial pyruvate carrier (MPC) in the occurrence of this metabolic inflexibility in wild-type (WT) and MPC1-deficient (MPC1def) flies that were exposed to diets with different sucrose concentrations for 15–25 days (Standard Diet: SD, Medium-Sucrose Diet: MSD, and High-Sucrose Diet: HSD). Our results showed that MPC1def flies had lower mitochondrial respiration rates than WT flies on the SD and MSD. However, when exposed to the HSD, WT flies displayed decreased mitochondrial respiration rates compared to MPC1def flies. WT flies exposed to the HSD also displayed increased proline contribution and slightly decreased MPC1 expression. Surprisingly, when fed the MSD and the HSD, few metabolites were altered in WT flies whereas MPC1def flies display significant accumulation of glycogen, glucose, fructose, lactate, and glycerol. Overall, this suggests that metabolic inflexibility starts to occur in WT flies after 15–25 days of exposure to the HSD whereas the MPC1def flies display metabolic inflexibility independently of the diet provided. This study thus highlights the involvement of MPC as an essential protein in Drosophila to maintain proper metabolic homeostasis during changes in dietary resources.